(untitled) (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Risk factors for early re-bleeding and in-hospital mortality following acute variceal hemorrhage (AVH) are incompletely understood. The aim of this study was to find out the risk factors for early re-bleeding within 5 days and in-hospital mortality after AVH in patients with cirrhosis. Method: This was an analytical cross-sectional study conducted in Department of Medicine, Patan Hospital, Patan Academy of Health Sciences (PAHS), Nepal from July 2021 to June 2022. The ethical clearance was obtained from the Institutional Review Committee-PAHS. Informed consent was taken from the patients. Patients aged >18 y with diagnosed case of liver cirrhosis and endoscopy confirmed variceal bleeding were enrolled. All cases of early re-bleeding within 5 days and in-hospital outcome were recorded. Result: In this study total 72 patients were enrolled. The mean age of our patients was 51.68 y. Sixty seven (93%) of the patients improved, 3(4.16%) had early re-bleeding and 5(6.9%) died during the same hospital admission. Univariate analysis showed that early re-bleeding was significantly associated with the high PT/INR (p<0.001) and high Child-Turcotte Pugh (CTP) score (p=0.032), whereas in-hospital mortality of patients was significantly associated with low Protein (p=0.044), high CTP score (p=0.041), high Model for End stage Liver Disease (MELD) score (p=0.002) and presence of gastric varices (p=0.008). Conclusion: High PT/INR and high CTP score are the risk factors of early re-bleeding after AVH in cirrhotic patients. Low Protein, high CTP and MELD scores, and presence of gastric varices are the factors associated with in-hospital mortality in these patients.